Bulk Metallic Glasses - Miller, Michael; Liaw, Peter; SpringerLink (Online service) (Boston, MA : Springer US, 2008)
Bulk Metallic Glasses explores an emerging field of materials known as bulk metallic glasses. It summarizes the rapid development of these materials over the last decade and includes documentation on diverse applications of bulk metallic glasses; from structural applications to microcomponents. Some of the applications covered are pressure sensors, microgears for motors, magnetic cores for power supplies, and nano-dies for replacing next generation DVDs. The chapters cover current theories and recent research including an atomistic theory of local topological fluctuations, atomistic simulations, and unique microstructures of these amorphous materials. Other topics include glass formation, glass forming ability, and the underlying mechanisms and physical insights of these criteria. The mechanical deformation of bulk metallic glasses, fatigue, fracture, and corrosion behaviors of these materials are also reviewed. Bulk Metallic Glasses is a valuable resource for graduate and under-graduate students as well as professors, engineers, and researchers.
Development and Applications of Late Transition Metal Bulk Metallic Glasses -- Atomistic Theory Of Metallic Liquids and Glasses -- Modeling: The Role Of Atomistic Simulations -- Evaluation Of Glass-Forming Ability -- Microstructure -- Deformation Behavior -- Fatigue And Fracture Behavior -- Corrosion Behavior.
Keywords: Materials science; Nanotechnology; Metals; Materials Science; Metallic Materials; Nanotechnology; Characterization and Evaluation of Materials; Ceramics, Glass, Composites, Natural Methods; Electronic books